(untitled) (Texas Journal of Engineering and Technology, 2024)
In this article, the method of mathematical planning of multifactorial experiments is used to determine the optimal values of the parameters of a potato digger equipped with an elastic rod intensifier, obtained in single-factorial experiments. It is assumed that the influence of factors on the evaluation criteria is fully explained by a second-order polynomial, and the experiments were carried out according to the Hartley-4 (X4) plan